C*-Algebras Associated with F_2^n Unimodal Dynamical Systems - Maistrenko, T. Yu.; Popovich, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider C*-algebras associated with simple unimodal one-dimensional ambiguous dynamical systems (f,R) with certain special restrictions. For these algebras, we present a complete classification of irreducible representations in Hilbert spaces and describe the dual space. As an example, we consider the one-parameter family f_μ(x) = μx(1 − x).